Aid effectiveness in the Caribbean : revisiting some old issues - Brunton, P. Desmond (CDB St. MichaelBB, 2000)
Looks at trends in aid flows; the effectiveness of aid; small states and the vulnerability issue; and, ways of enhancing aid effectiveness.